Playing basketball and volleyball during adolescence is associated with higher bone mineral density in old age: the Bunkyo Health Study - Otsuka, Hikaru; Tabata, Hiroki; Shi, Huicong; Sugimoto, Mari; Kaga, Hideyoshi; Someya, Yuki; Naito, Hitoshi; Ito, Naoaki; Abudurezake, Abulaiti; Umemura, Futaba; Tajima, Tsubasa; Kakehi, Saori; et al. (Frontiers in Physiology, 2023)
Introduction: Exercise is beneficial for increasing areal bone mineral density (aBMD) in adolescence and maintaining it in old age. Moreover, high-impact sports are more effective than low-impact sports in increasing aBMD. This study aimed to determine the types of adolescent sports played in schoolbased sports clubs associated with aBMD in old age.2 Methods: In total, 1596 older adults (681 men and 915 women, age: 65-84 years) living in an urban area of Japan were evaluated for the femoral neck and lumbar spine aBMD using dual-energy X-ray absorptiometry. The association between adolescent sports played in sports clubs and aBMD in old age was analyzed using multiple regression analysis, with femoral neck and lumbar spine aBMD as dependent variables, and sports type and participant characteristics such as age, body weight, and serum 25-hydroxyvitamin D [25(OH)D] level, as independent variables. Results: For the femoral neck, basketball was associated with aBMD in older men (β=0.079, P < 0.05) and women (β=0.08, P < 0.01), whereas current body weight and 25 [OH] D level were associated with aBMD in both sexes. For the lumbar spine, volleyball (β=0.08, P < 0.01) and swimming (β=0.06, P < 0.05) was significantly associated with lumbar spine aBMD, whereas current body weight, 25(OH)D, and diabetes mellitus were associated with aBMD in older women. Conclusion: Both men and women who played basketball in adolescence had higher femoral neck aBMDs in old age. Moreover, women who played volleyball in adolescence had higher lumbar spine aBMDs in old age.